2020
DOI: 10.1101/2020.05.10.086926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief sensory deprivation triggers cell type-specific structural and functional plasticity in olfactory bulb neurons

Abstract: Can alterations in experience trigger different plastic modifications in neuronal structure and function, and if so, how do they integrate at the cellular level? To address this question, we interrogated circuitry in the mouse olfactory bulb responsible for the earliest steps in odour processing. We induced experience-dependent plasticity in mice by blocking one nostril for a day, a minimally-invasive manipulation which leaves the sensory organ undamaged and is akin to the natural transient blockage suffered d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…Having shown that the DAT-tdTomato mouse line labels olfactory bulb neurons that are predominantly dopaminergic but include a distinct subset of calretinin-positive cells, we went on to use this line for naturally-relevant manipulations of sensory experience (Fokkens et al ., 2012; Galliano et al, 2021). In juvenile mice from postnatal day (P)27, we induced brief 1- or 3-day periods of sensory deprivation without damaging the olfactory epithelium, via unilateral naris occlusion with a plastic plug (Fig.2A; Cummings et al ., 1997; Kikuta et al ., 2015; Cheetham et al ., 2016; Galliano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having shown that the DAT-tdTomato mouse line labels olfactory bulb neurons that are predominantly dopaminergic but include a distinct subset of calretinin-positive cells, we went on to use this line for naturally-relevant manipulations of sensory experience (Fokkens et al ., 2012; Galliano et al, 2021). In juvenile mice from postnatal day (P)27, we induced brief 1- or 3-day periods of sensory deprivation without damaging the olfactory epithelium, via unilateral naris occlusion with a plastic plug (Fig.2A; Cummings et al ., 1997; Kikuta et al ., 2015; Cheetham et al ., 2016; Galliano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Our data showing decreased TH expression after olfactory sensory deprivation are entirely consistent with a large body of prior work describing this effect (Nadi et al ., 1981; Baker et al ., 1983, 1984, 1993, 1999; Kosaka et al ., 1987; Baker, 1990; Stone et al ., 1990; Cho et al ., 1996; Philpot et al ., 1998; Saino-Saito et al ., 2004; Bastien-Dionne et al ., 2010; Cave et al ., 2010; Weiss et al ., 2011; Grier et al ., 2016), including some indications that it can occur after relatively brief manipulations (Cho et al ., 1996; Akiba et al ., 2007; Chand et al ., 2015; Galliano et al, 2021). It is novel, however, that our methodological approach demonstrated activity-dependent TH alterations in cells identified in an entirely TH-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most essential components of the AIS is the cytoskeletal-associated protein, Ankyrin-G (AnkG) 40 . Previous studies have shown that shorter or fewer AISes measured by AnkG are indicative of impairments to the neurons physiology, such as a decrease in excitability 39,41,42 . We first co-stained OB sections with AnkG and Tbx21, an OB projection neuron-specific marker, and confirmed that the vast majority of AnkG+ AISes present in the EPL and MCL are derived from TCs and MCs, respectively (Supplementary Fig.…”
Section: Alterations In the Axon Initial Segment Of Tufted Cells Following 10-week Coimentioning
confidence: 99%
“…To examine the alterations in cellular activity of the OB projection neuros, we stained OBs with an antibody against phoso-S6 ribosomal protein (pS6), one of neuronal activity markers 43 . A recent study demonstrated that pS6 is an exceptional activity marker for OB projection neurons, and that naris occlusion is capable of significantly reducing the expression of pS6 among projection neurons on the ipsilateral OB 41 . It is also worth noting that the vast majority of pS6expressing projection neuron somata were double-positive for Tbx21 (Supplementary Fig.…”
Section: Reduction In Tufted Cell Activity Following 10-week Coimentioning
confidence: 99%